Fighting Infectious Disease: Evidence from Sweden 1870-1940 - Volha Lazuka; Luciana Quaranta; Tommy Bengtsson (Institute for the Study of Labor (IZA), 2015)
Fighting infectious disease in the past, much like today, focused on isolating the disease and thereby stopping its spread. New insights into the modes of transmission and the causal agents in the mid-nineteenth century, together with fear of new epidemic outbreaks, motivated public investments aimed at reducing mortality from infectious disease. Combining longitudinal individual-level data on 17,000 children in a rural/semi-urban region in southern Sweden with parish-level data on public health investment from local ledger registers, we explore the effects of public health initiatives, such as the establishment of isolation hospitals and improved midwifery, on infant and child mortality. Using a difference-in-differences approach, we find that the establishment of isolation hospitals in the mid-1890s had been efficient in reducing child mortality, while the reformation of the midwife system after 1900s led to the decline in infant mortality, both by a magnitude of more than 50 per cent.
Keywords: I14; I18; H51; J18; 330; public health investment; infectious diseases; mortality; children; Sweden